Metastasizing Maxillary Ameloblastoma: Report of a Case with Molecular Characterization - Matteo Rotellini; Giandomenico Maggiore; Massimo Trovati; Massimo Squadrelli Saraceno; Alessandro Franchi (Stilus Optimus, 2016)
Background: Ameloblastoma is a benign odontogenic tumour that may exhibit aggressive biological behaviour with local recurrence and metastasis following initial surgical resection. Surgery is the most acceptable modality of treatment, even if a biological approach is currently on study. We report a case of maxillary ameloblastoma with development of neck and brain metastases after repeated local recurrences. Molecular analysis was performed with the aim to better characterize this neoplasm and its peculiar behaviour. Methods: We investigated the status of tumour protein p53 (TP53), epidermal growth factor receptor (EGFR), B-Raf proto-oncogene (BRAF) and human epidermal growth factor receptor 2 (HER2) genes with immunohistochemical, fluorescent in situ hybridization and/or direct sequencing in order to clarify their possible role in the development of this neoplasm and the possibility of a targeted treatment. Results: The histological appearance of the tumour was the same in the primary lesion, in the recurrence and in the metastases. EGFR positivity was present in the recurrence and the brain metastasis, while HER2 was negative in all samples tested. Fluorescent in situ hybridization analysis for EGFR showed disomy of neoplastic cells. Direct DNA sequencing of TP53 gene exons 5 - 9 was carried out in tumour samples from the infratemporal recurrence and brain metastasis, with no mutational alteration detected. Similarly, sequencing analysis of BRAF exon 15 (V600) and EGFR gene showed wild type results in all samples tested. Conclusions: Further studies are needed to identify molecular pathways that may provide an opportunity of alternative treatments and/or new potential predictive markers of local and distant spread of this rare tumour.